Community Participation and Social Justice in Urban Sustainability Programs - Irianto, Eko; Mulia, Emil; Zahra, Siti (Journal Social Humanity Perspective, 2025)
This paper looks at how the community can play a significant role in promoting social justice in urban sustainability initiatives and how the practice of grassroots is relevant in achieving equitable and sustainable urban futures. Although sustainability initiatives have become the norm and are widely applied, these initiatives are not typically approached with managerial techniques framing them as a justice-providing mechanism but as a procedural requirement, which leads to exclusion and tokenism and marginalizes vulnerable populations. This study relies on a qualitative research design based on the in-depth interviews, focus groups discussions, and field observation within urban populations in an attempt to understand the experiences of participation, the challenge, and redefinition of participation as experienced by the bottom-up. The results show that communities implement justice in a variety of ways, among which are integration of local knowledge, solidarity networks, inclusion and engagement strategies, grassroots advocacy, and the everyday ethics of care. The practices exemplify the ways distributive, procedural, and relational aspects of justice are integrated into community everyday life and tend to fill gaps that may exist in formal institutions. This paper presents a thesis that sustainability management should remake participation not as symbolic gesture but as power-sharing process that considers communities as co-producers of justice and sustainability. This necessitates that managers should integrate equity as a guiding concept, appreciate community-based practices as a knowledge system that is legitimate and reconfigure governance institutions to enable true collaboration. This study will lead to advances in management literature by aligning sustainability, social justice and community governance, through the centrality of justice as a part of participation, and in practical terms, to the policymaker and practitioner.